Effects of aerobic and anaerobic exercise on glucose, lipid, and inflammation-related gene expression in the brain tissue of streptozotocin-induced diabetic rat model - Kilic, Yakup; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Ozdemir, Emrah; Ugurlu, Fatih Mehmet; Pala, Ragip; Ayilgan, Ercan (Bmc, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a common metabolic disease characterized by elevated blood glucose levels accompanied by inadequate insulin secretion. In this study, we aimed to determine the expression levels of PEPCK, FAS, INSIG-1 and TNF-alpha genes, which play a key role in metabolism and inflammation processes, in brain tissue of rats with streptozotocin (STZ)-induced diabetes and to investigate how these gene expressions are affected by different exercise protocols.MethodsIn this study, 40 male Wistar albino rats were randomly divided into four groups: Control group (C), Diabetes Sedentary group (DS), Diabetes Heavy Exercise group (DHE) and Diabetes Light Exercise group (DLE). Diabetes was induced by a single dose of intraperitoneally administered streptozotocin (STZ, 60 mg/kg). After diabetes induction, rats were subjected to treadmill exercise 5 days a week for 6 weeks. 24 h after the last exercise session, rats were sacrificed by decapitation and brain tissues were sent to the laboratory for molecular analysis.ResultsA significant decrease in FAS (p = 0.002) and TNF-alpha (p = 0.044) levels was observed in the DHE group, while a significant increase in PEPCK (p = 0.009) and INSIG1 (p = 0.019) levels and a significant decrease in FAS (p = 0.037) and TNF-alpha (p = 0.014) levels were found in the DLE group. In addition, blood glucose levels were significantly decreased in the exercise groups compared to the diabetic sedentary group (p = 0.001).ConclusionThis study revealed that exercise protocols of different intensities induce significant changes in the expression levels of some metabolic and inflammatory genes in brain tissue and decrease blood glucose levels in rats with streptozotocin-induced diabetes model. The findings suggest that exercise may partially modulate the molecular processes in the central nervous system of diabetes and may offer potential therapeutic contributions.
Keywords: Diabetes; Exercise; Brain tissue; Gene expression